Case Report: A unique case of secondary hemophagocytic lymphohistiocytosis from ehrlichiosis infection - Hlaing, Swe Swe; Kurian, Christine Jane; Tan, Jennie; Behling, Eric; Hussein, Ahmed Kamel Abou (Frontiers in Hematology, 2022)
Hemophagocytic lymphohistiocytosis (HLH) is a highly detrimental syndrome that can progress to multiorgan failure, necessitating the resources of an intensive care unit, with a mortality rate as high as 40%. Secondary HLH is usually triggered by infection, most often from a viral infection or malignancy. Management of HLH in adults is challenging as treatment algorithms targeting hyperinflammation are based on pediatric protocols, such as HLH-94 and HLH-2004. To our knowledge, there are only a few reported cases of HLH secondary to ehrlichiosis infection and none in elderly patients with multiple comorbidities. Here, we present a unique case of HLH secondary to ehrlichiosis infection in an 82-year-old female successfully treated with antibiotics and steroids.